HARMONISATION OF MACROPROLACTIN REPORTING - Sthaneshwar, Pavai; Thambiah, Subashini C.; Ratnasingam3, Jeyakantha (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND The post-analytical phase is the last phase of the total testing process and it is an important step since it maximises the quality and effectiveness of laboratory information. Macroprolactin is a well-known analytical problem in laboratory diagnostics. There is no agreement on when to screen for macroprolactin in patients with hyperprolactinaemia nor is there consensus on the reporting, terminology and reference intervals for macroprolactin. METHODOLOGY To create a consensus document that standardises the reporting of prolactin results after precipitation with polyethylene glycol (PEG) to minimise errors in result interpretation. As a part of the joint initiative by the Chapter of Chemical Pathology and Metabolic Medicine, College of Pathologists, Academy of Medicine Malaysia and the Malaysian Association of Clinical Biochemists to harmonise the laboratory reporting of macroprolactin in Malaysia, an audit was conducted to obtain feedback from endocrino-logists from public, private and academic institutions on macroprolactin reporting. The questionnaire included the level of prolactin that was considered as hyperprolactinaemia, its cut-off value in males and female and whether screening for macroprolactin should be clinician-centred or laboratorycentred. It also addressed post-PEG precipitation, whether the report should specify the presence of macroprolactin and the preferred reporting format. RESULTS Responses were obtained from 33 endocrinologists. The majority (81%) used reference limits given rather than a fixed cut-off of 700 m IU/L and 70% used a sex-specific range. More than half (69%) favoured that the laboratory should screen for macroprolactin in all samples with high prolactin. On report format, 61.5% preferred the use of postPEG monomeric reference ranges and 100% required the laboratory to indicate the presence of macroprolactin. CONCLUSION The laboratory working group will consider the responses from endocrinologists in preparing the consensus recommendations on reporting macroprolactin and the reference intervals.